A Bioimpedance-Based Device to Assess the Volume Conduction Properties of the Tongue in Neurological Disorders Affecting Bulbar function - Xuesong Luo; Hilda V. Gutierrez Pulido; Seward Rutkove; Benjamin Sanchez (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Current instruments for bulbar assessment exhibit technical limitations that hinder the execution of clinical studies. The volume conduction properties (VCP) of the tongue reflect ionic content and myofiber integrity and they can serve as a new biomarker for evaluating neurological disorders with bulbar dysfunction. Methods: We designed a standalone bioimpedance measurement system that enables accurate, multi-frequency measurement of tongue anisotropic VCP including conductivity and relative permittivity. The system includes a tongue depressor with 16 non-invasive surface sensors for electrical contact with the tongue at directions 0 $^{° }$ , 45 $^{° }$ , 90 $^{° }$ and 150 $^{° }$ . The depressor is interfaced with the tongue electronic system with Bluetooth connectivity, and a smartphone application. De-identified patient data is sent by email. Results: We first determined the accuracy of the hardware performing phantom measurements mimicking a broad range of tongue values and determined the error to be $< $ 1%. We then validated our new technology measuring a cohort of 7 healthy human subjects under Institutional Review Board approval. Conclusions: None of the subjects who participated suffered discomfort or gag reflexes. The novel technique presented for intra-oral assessment of tongue VCP provides standard, objective and quantitative data potentially sensitive to alterations in tongue internal structure and composition.